Knowledge Regarding Health Promotional Measures of Infant among Mothers Attending Pediatric OPD of Universal College of Medical Sciences - Bhusal, Chet Kant; Bhattarai, Sigma; Kafle, Raju; Shrestha, Rubina (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Infant and child health status depends upon knowledge of mothers regarding health promotional measures. This study aimed to determine knowledge and its associated factors regarding health promotional measures of infants amongst the mothers attending pediatrics outpatient department of Universal College of Medical Sciences Teaching Hospital, Bhairahawa, Rupandehi, Nepal. MATERIAL AND METHODS Hospital based cross-sectional study was conducted in Universal College of Medical Sciences Teaching Hospital, Bhairahawa, Rupandehi, Nepal among 414 mothers attending pediatrics outpatient department from June 2019 to March 2020. Bivariate and multivariate logistic regressions were used to explore associations between different factors with health promotional measures. RESULTS The mean age and family size was 25.89 ±4.81 and 5.94 ±2.48 respectively. A total of 73.2% mothers have good knowledge of health promotional measures. Mothers greater than 20 years (AOR =8.13, CI: 2.16-30.67), Dalit (AOR=0.02, CI: 0.003-0.16), living in rural area (AOR=0.27, CI: 0.08-0.61), family size greater than 5 (AOR =3.99, CI: 1.37-11.59), below SLC education (AOR=0.29, CI: (0.09-0.88) and fathers with SLC and above education (AOR=25.40, CI: 4.54-142.0), fathers engaged in non-agricultural work (AOR =4.78, CI: 1.80-12.68) and birth space of index child greater than two years (AOR =5.88, CI: 1.48-23.55) were significantly associated with knowledge of health promotional measures. CONCLUSIONS Mothers’ age, caste, residence, family size, education of parents, occupation of father and birth space of index child were found to be independent associated factors of knowledge. Thus policy makers should provide specific education regarding health promotional measures to both parents focusing rural area. Similarly, local Government needs to subsidize in reducing teenage marriage.